Respuesta :
Answer:
x= [tex]\frac{19}{8}[/tex]
Step-by-step explanation:
8(x−3)−(6−2x)=2(x+2)−5(5−2)
Step 1: Simplify both sides of the equation.
8(x−3)−(6−2x)=2(x+2)−5(5−2)
8(x−3)+−1(6−2x)=2(x+2)−5(5−2)(Distribute the Negative Sign)
8(x−3)+(−1)(6)+−1(−2x)=2(x+2)−5(5−2)
8(x−3)+−6+2x=2(x+2)−5(5−2)
(8)(x)+(8)(−3)+−6+2x=(2)(x)+(2)(2)+−5(5−2)(Distribute)
8x+−24+−6+2x=2x+4+−15
(8x+2x)+(−24+−6)=(2x)+(4+−15)(Combine Like Terms)
10x+−30=2x+−11
10x−30=2x−11
Step 2: Subtract 2x from both sides.
10x−30−2x=2x−11−2x
8x−30=−11
Step 3: Add 30 to both sides.
8x−30+30=−11+30
8x=19
Step 4: Divide both sides by 8.
8x/8=19/8
Answer: x=[tex]\frac{19}{8}[/tex]
8(x - 3) - (6 - 2x) = 2(x + 2) - 5(5 - 2)
8*x - 8*3 - 6 + 2x = 2*x + 2*2 - 5*3
8x - 24 - 6 + 2x = 2x + 4 - 15 ( Cancel equal terms on both sides of the equation)
8x - 24 - 6 = 4 - 15
8x - 30 = -11
8x = -11 + 30
8x = 19
x = 19/8